SEND and SENCO support. (2nd March 2020) - Mulholland, Margaret
Abstract : The high numbers of pupils with SEN are putting a huge strain on school finances – and on SENCOs themselves. Margaret Mulholland looks at some tenets of best practice, what Ofsted wants to see, and how schools can best support their SENCOs